Preparation of Polymeric Nanomaterials Using Emulsion Polymerization. (8th October 2021) - Sahoo, Satyajeet; Gopalan, Anitha; Ramesh, S.; Nirmala, P.; Ramkumar, G.; Agnes Shifani, S.; Subbiah, Ram; Isaac JoshuaRamesh Lalvani, J.
Abstract : Nanoparticles are said to be active particles which are entrapped in the surface of the polymeric core. Since nanoparticles were used in medical and biotechnological fields, there is a great demand in the preparation of nanoparticles. Nanoparticles are prepared from different substances; mainly, polymer material is used in the field of preparing nanomaterials. There are different methods involved in the preparation of nanoparticles from the polymer. Various experiments and research studies were carried out on the basic preparation of nanoparticles. Emulsion polymerization could be used to make polymeric nanoparticles with a high solid concentration without the need of surfactants. To make carboxylate polystyrene beads or amidine polystyrene nanoparticles, polymeric nanocolloids containing surface functional groups were produced. In this research, the preparation of nanoparticles from emulsion polymerization is represented along with the size and distribution material.